ANALYSIS OF FACTORS INFLUENCING THE USE OF THE TUBECTOMY METHOD IN FERTILE COUPLES: A LITERATURE REVIEW - Sulistyowati, Agus; Wijayanti, Dini Prastyo; Listari, Risti Puji (Nurse and Health: Jurnal Keperawatan, 2024)
Background: The use of tubectomy contraception is one way to control birth rates and improve reproductive health. Tubectomy is a permanent form of contraception that involves blocking or sealing the fallopian tubes to prevent the egg from reaching the uterus for fertilization. This article analyzes the factors that influence the use of tubectomy contraception among couples of childbearing ages. Objective: This literature review aims to identify factors that influence the use of the tubectomy method in fertile couples. Design: This research design is a literature review. Data Sources: Search for articles using three journal databases, namely Google Scholar, PubMed, and ScienceDirect. Reviews Methods: Used PRISM flow diagram to find a total of 6 articles that meet the inclusion criteria reviewed. Results: Inclusion criteria include full text articles from 2015-2024 published from national or international journals. Article types are quasi-experimental and case studies. Five articles meet the inclusion criteria. the various techniques used in tubectomy, the benefits and risks associated with the procedure, and its effectiveness in preventing pregnancy. Tubectomy can be done through different methods. Conclusion: Tubectomy is crucial to recognize and address the social stigmas surrounding tubectomy in order to create a more supportive and understanding environment for individuals seeking this form of birth control. By promoting open dialogue and challenging misconceptions, we can work towards creating a more inclusive society where individuals feel empowered to make informed decisions about their reproductive health.